2020
DOI: 10.1038/s41467-020-18376-x
|View full text |Cite
|
Sign up to set email alerts
|

Raman-guided subcellular pharmaco-metabolomics for metastatic melanoma cells

Abstract: Non-invasively probing metabolites within single live cells is highly desired but challenging. Here we utilize Raman spectro-microscopy for spatial mapping of metabolites within single cells, with the specific goal of identifying druggable metabolic susceptibilities from a series of patient-derived melanoma cell lines. Each cell line represents a different characteristic level of cancer cell de-differentiation. First, with Raman spectroscopy, followed by stimulated Raman scattering (SRS) microscopy and transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 79 publications
1
96
0
Order By: Relevance
“…A study by Tirinato et al demonstrated the capability of functional characterization of lipid droplets in cancer stem cells (CSCs) by Raman spectroscopy, and confirmed lipid droplets as a distinctive mark of CSCs in colorectal cancer [40]. Similarly, lipid upregulation and reprogramming was observed by Raman spectroscopy in cells of prostate cancer [23], lung cancer [41], and melanoma [42,43].…”
Section: Investigation Of Lipid Metabolism In Cancer Cellsmentioning
confidence: 92%
See 2 more Smart Citations
“…A study by Tirinato et al demonstrated the capability of functional characterization of lipid droplets in cancer stem cells (CSCs) by Raman spectroscopy, and confirmed lipid droplets as a distinctive mark of CSCs in colorectal cancer [40]. Similarly, lipid upregulation and reprogramming was observed by Raman spectroscopy in cells of prostate cancer [23], lung cancer [41], and melanoma [42,43].…”
Section: Investigation Of Lipid Metabolism In Cancer Cellsmentioning
confidence: 92%
“…They monitored lipids along varying depths of mouse skin, as well as DMSO penetrating into the skin. Since then, CRS microscopy was used extensively in lipid imaging with structural diversity tightly associated with their biological functions [43,[46][47][48][49][50][51][52][53][54][55].…”
Section: Investigation Of Lipid Metabolism In Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The generated CH 2 /CH 3 ratiometric images indeed nicely resolved a decreasing trend from melanocytic M262 cells toward mesenchymal M381 cells, implying that, more differentiated cells are relatively richer in lipids. In addition, hyperspectral SRS microscopy was utilized to analyze the composition of these sub‐cellular LDs at a spatial resolution of ∼450 nm [70] …”
Section: Coherent Raman Scatteringmentioning
confidence: 99%
“…Using with Raman spectroscopy, followed by stimulated Raman scattering (SRS) microscopy and Raman-guided subcellular pharmaco-metabolomics in metastatic melanoma cells revealed intracellular lipid droplets that helped identify a previously unknown susceptibility of lipid mono-unsaturation within de-differentiated mesenchymal cells with innate resistance to BRAF inhibition (Du et al 2020 ). Application of 31 P NMR was shown to hold potential of expanding the coverage of the metabolome by detecting phosphorus-containing metabolites (Bhinderwala et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%